FAKTOR – FAKTOR YANG MEMPENGARUHI UNDERPRICING IPO DI BURSA EFEK INDONESIA PERIODE 2008 - 2013 - Diah Dewi Permanisuci (JURNAL MANAJEMEN, 2015)
This research has objective to empirical evidence that independent variables in this research ex financial leverage, reputastion auditor, return on assets, reputation underwriter, company size, firm age can be effect to underpricing companies listed in Indonesia Stock Exchange periods 2008-2012. This research uses data from all companies that listed in Indonesia stock Exchange periods 2008 – 2012. Samples are used as sixthy companies. This research show the occurrence of underpricing in initial public offering. There is variable effect auditor, company size, firm age, eith the level of underpricing that listed in Indonesia stock exchange. There is nothing influence financial leverage, reputation underwriter, return on asset with the level of underpriccing that listed in Indonesia stock exchange Keywords:.reputation underwriter, reputation auditor, company size, firm age, return on assets, financial leverage, levels of underpricing.